ENDOVASCULAR MANAGEMENT OF ACUTE TANDEM OCCLUSION STROKE - Ayman Gamea, Omar Osman, Mohamed Abdala Abbas, Ahmed elbassiouny (Chelonian Research Foundation, 2025)
Acute ischemic stroke caused by tandem occlusion is characterized by a blockage or severe narrowing of the cervical internal carotid artery along with an embolic obstruction in a major intracranial vessel, such as the terminal carotid or proximal middle cerebral arteries. This condition accounts for 10–20% of all ischemic strokes. Without treatment, studies estimate that 40–69% of affected patients either suffer severe disability or do not survive. Tandem occlusion is associated with poor prognosis in acute stroke management due to its high mortality and morbidity rates, as well as its low response to intravenous tissue plasminogen activator (tPA). However, endovascular treatment has demonstrated advantages in restoring blood flow in large vessel occlusions, preserving the cerebral penumbra, and improving clinical outcomes. Current treatment guidelines recommend an initial administration of intravenous thrombolytic therapy, followed by endovascular thrombectomy. Despite these recommendations, there is still no standardized endovascular approach specifically for managing this stroke subtype.